The relationship of emotional abuse, self-value and conflict resolution needs in secondary school students - Erses, Tümen; Kiliç, Yalin; Berkmen, Bengü (Frontiers in Psychology, 2022)
The most crucial period for the teenagers is the secondary school period. The affection and knowledge which lead the student to build up his or her own self individuality, develop positive relationships and cope with possible conflicts must be given to her or him by his or her family and neighbourhood. The aim of this study is to analyze the correlation amongst the self respect, the need for the solution of the conflict, social anxiety and emotional exploitation within the range of the middle school students. The afore mentioned research is such a kind of desriptive study which used one of the correlational survey research models , the quantitative method. In addition to the Personal Data Collection Document, the Scales of the Need of Conflict Resolution, Emotional Exploitation, the Rosenberg Self Respect Scale and the Social Anxiety Scale for the Teenagers are used. The research universe of this study is composed of 10.196 middle school students studying in the 6th, 7th and the 8th year, at the public schools of the Ministry of Education of the TRNC. The sample group of the research is constituted by 530 volunteer middle school students respectively from Famagusta, Guzelyurt, Lefke, Nicosia and Kyrenia. The AMOS 2.1 and the SPSS 25 are used in order to resolve the data collected. The study carried out through the Structural Equality Method verifies that there is an agent role of the Need for the Conflict Resolution in between the Self Respect and Emotional Exploitation. However, there can not be verified any relation in between the Self Respect and the Social Anxiety within the agent role of the Need for the Conflict Resolution. There has been verified meaningful and positive correlations amongst through the marks of the students taken from the NCR and the SAST, the NCR and the EES, the NCR and the RSRS, the SAST and the RSRS, the SAST and the EES, the EES and the RSRS.